PENERAPAN BOOKLET BERBASIS PROBLEM BEST LEARNING UPAYA PENINGKATAN PEMAHAMAN LITERASI MATERI TANDA BACA MURID KELAS 3 - Zahra Rika Karmelia; Rakhmawati Mulyani; Aura Laila Maghviroh; Pandu Budi Pratama; Panca Dewi Purwati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to improve the literacy comprehension of third-grade elementary students on punctuation marks through the implementation of a Problem-Based Learning (PBL)- based booklet. The background of this study stems from the low ability of students to use punctuation correctly in reading and writing activities. The research employed a mixed- method approach combining qualitative and quantitative techniques to obtain comprehensive data. The booklet was implemented using a contextual reading text titled “Bermain Lompat Tali” (Playing Jump Rope). The findings indicate that the PBL-based booklet effectively enhances students’ understanding of punctuation functions, their ability to read with proper intonation, and their accuracy in writing sentences with correct punctuation. Furthermore, this approach increased students’ learning motivation and active participation during the lessons. Therefore, the development of a PBL-based booklet can serve as an effective alternative to strengthen students’ basic literacy skills in elementary education.